UPACARA ADAT TIWAH MASYARAKAT DAYAK DI KALIMANTAN TENGAH - Renhat Bonxy; Christina Rochayanti; Panji Dwi Ashriyanto (Jurnal Paradigma, 2018)
This research is to know how the meaning of bone removal procession on Tiwah inCentral Kalimantan and to know what is contained message in the procession of boneremoval, this reasearch is done by doing semiotic analysis on the symbols and signs thatare in procession. The type of this research is qualitative interpretative by using semioticanalysis method, semiotics is a science that examines the sign. Data collection on thisreasearch using observation techniques , study of literature, interview and documentation.The technique to knowing the meaning of the bone removal process is by analyzing thesigns present in the procession. Based on the results of the research we know that, theprocession of bone removal on tiwah has a very deep meaning for life. This processionshowing the affection and caring from dayak society to their relatives and a hope to havea better life. There is a myth like Roland Barthes says there is a myth but the truth are stillunknownable the truthness. the myth of bone removal after performing ritual removal ofbone is a prayer and a hope that has been presented to the Creator.